Hydration Energy-Dependent Ion Intercalation on Graphite and the Asymmetric Electrowetting - Shao, Wan (Langmuir : the ACS journal of surfaces and colloids, 2023)
Ion intercalation in graphite is widely used in desalination, batteries, and graphene stripping; it has high value in the fields of industry and research. However, selective ion transport, particularly (de)hydration energy and the hydration shell effect on the intercalation of ions into the graphite interlayer spaces, is still unclear. Here, we report low-voltage ion intercalation as observed by electrowetting on highly oriented pyrolytic graphite of an aqueous drop containing various inorganic salts. The electrowetting response exhibits asymmetric behavior with no contact angle change for the negative polarity and a threshold voltage for the onset of the contact angle change for the positive polarity. To explain the asymmetric electrowetting behavior and quantitatively predict the threshold voltage, we developed a physical model based on the hydration shell energy and size of the ion that undergoes partial breaking/deformation during the co-intercalation into the spaces between graphite layers. Electrowetting experiments using ions with various hydration energies and hydration radii were performed to confirm the prediction of the model. Further, we show a strategy to make the electrowetting response of LiCl drops symmetric via tuning the hydration energy of the Li+ ions using a binary solvent of a glycerol-water mixture. This article will provide an understanding of the hydration (solvation) energy dependence intercalation mechanism in graphite for electrowetting, which underpins various processes such as ion battery applications and the graphene exfoliation process